Analisis Deskriptif Kinerja BUMD Di Propinsi Jambi - Safri, Muhammad; Fitriaty, Fitriaty (Jurnal Dinamika Manajemen, 2022)
Regional Owned Enterprises (BUMD) is a business entity established by the regional government with the aim of carrying out regional development through providing services to the community, organizing public benefits and increasing local revenue (PAD). For this reason, BUMD must have good business performance. BUMD Management is expected to fulfill and take advantage of market attractiveness and resources and carry out business development to take advantage of business opportunities that have an impact on improving performance. This study aims to measure management in meeting market attractiveness and resources and customer needs so that it can have an impact on development business and can increase local revenue (PAD). The internal analysis unit is BUMD in Jambi Province, City and Regency. The unit of observation in this study is the management of BUMD and the heads of business units in the company and customers. The research method used is descriptive. From the results of the research it was revealed that BUMD in Jambi Province, in improving business performance it is necessary to develop new potentials by increasing HR competencies to be able to meet market demands.